KAJIAN SUSTAINABLE DESIGN PADA RESTORAN KOOD (LPPM Institut Desain dan Bisnis Bali, 2024)
Sustainable design can be described as design that is able to meet the needs of today's society without compromising the ability of future generations to meet their needs. The urgency of this research is because the interior is the environment closest to humans and is the object where various human activities take place within it. The problem raised in this research is how to implement sustainable design in public spaces. In this research, a case study was taken at a restaurant with a plant based concept located around the Sanur tourist area, Denpasar Bali. To support this activity, the interior and architecture of the restaurant were designed to support the concept of this restaurant where various sustainable architectural and interior principles are also applied here. The research method used is a qualitative descriptive method. Energy saving efforts are implemented by maximizing natural lighting from glass openings and roof panels. The use of natural ventilation is carried out by minimizing the use of air conditioning, and maximizing cross ventilation through openings and rosters. Some vegetation functions as a pollution barrier. The use of interior materials and the choice of furniture in the restaurant refers to a sustainable, environmentally friendly concept. Red brick material, terracotta roster and terracotta flooring made from natural materials Efforts to reuse furniture materials also support sustainable design including construction materials that can be disassembled. The self-service system and the empowerment of local farmers also support sustainability from a social aspect. So that both social, economic and environmental aspects of the restaurant can be fulfilled.